International Universities in the Arab World: What is Their Place? - Anderson, Lisa (International Higher Education, 2017)
International institutions of higher education—from American-style universities to international branch campuses—have proliferated in the Arab world in the last several decades in response to both increasing demand for university places and declining quality in regional higher education. But are these institutions really taking root, or are the demands of international recruitment and rankings isolating them from their local and regional communities?